MALAY HOUSE, AN UNIQUENESS OF ARCHITETURAL DESIGN FORM - Yohannes Firzal (Local Wisdom : Jurnal Ilmiah Kajian Kearifan Lokal, 2011)
Malay houses almost always identifying through building raise on the pile, saddle roof and repeated gable-finials decorative that make them as a local distinct uniqueness. This uniqueness, which could be the strongest features, have brought significant cultural value and influencies to the development of building architecture. Gable horn, part of gable-finials, known as traditional roof decorative element has architectural similarities in the broad area coverage. Not only in traditional building of the archipelago, but also found strong evidence has similarities with decorative elements used on gable-finials in the region surrounding Astronesia such as; South East Asia, Malanesia, Micronesia, Polynesia and Madagascar. This has made identifying characteristic strong decorative elements.Gable horn become one hallmark of traditional architecture Astronesia region. Values contained not only from an architectural point of view, but can develop in accordance with their respective regional culture. The study was based on literature review and field surveyed to observed the presence of gable horn of Malay architecture traditional building. How variant element that can be encountered and became the origin to architectural presedent. Indeed, eventhough there are some varieties and forms of architectural elements throughout the archipelago, three major elements of raise on the pile, saddle roof and gable finial are become the most important characteristic of Malay house.